2014
DOI: 10.3892/mmr.2014.2205
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-21 regulation of the progression of viral myocarditis to dilated cardiomyopathy

Abstract: Abstract. MicroRNAs (miRNAs) comprise a broad class of small non-coding RNAs that control the expression of complementary target messenger RNAs. The dysregulation of miRNAs by several mechanisms has been described in various disease states, including cardiac disease. Although an etiological link between viral myocarditis (VMC) and idiopathic dilated cardiomyopathy (DCM) has long been recognized, the true extent of this association is uncertain. Previous studies of the two diseases have focused on protein degra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 38 publications
2
36
1
Order By: Relevance
“…MiR-21 is crucial in a number of biological functions and diseases, including development, cancer, cardiovascular diseases and inflammation [60]. In previous study, we found that miR-21 had a positive function in mitochondrial translation, which was sufficient to reduce blood pressure and alleviate cardiac hypertrophy in spontaneous hypertension rats [39].…”
Section: Discussionmentioning
confidence: 99%
“…MiR-21 is crucial in a number of biological functions and diseases, including development, cancer, cardiovascular diseases and inflammation [60]. In previous study, we found that miR-21 had a positive function in mitochondrial translation, which was sufficient to reduce blood pressure and alleviate cardiac hypertrophy in spontaneous hypertension rats [39].…”
Section: Discussionmentioning
confidence: 99%
“…Mouse model studies have reported a protective role for miR21 antagonism in heart fibrosis development (Figure 4) 203204 . Moreover, small molecule antagonism of miR21 205 has shown a marked protective effect in several mouse fibrosis models 168 .…”
Section: Metabolic Dysregulation In Diabetes and Ckdmentioning
confidence: 99%
“…Nevertheless, the quantification of miR-208b and miR-499 in myocarditis can potentially be used to determine the severity of the disease [91,127]. Pointing into the same direction are findings that describe miR-21 as an indicator for the transition of chronic myocarditis into dilated cardiomyopathy [128]. These results allow for a disease monitoring in known myocarditis -again only results from cellular analyses of cardiac tissue were reported.…”
Section: Infective Carditismentioning
confidence: 99%